Ill-health and transitions to part-time work and self-employment among older workers - Zucchelli, E.; Harris, Mark; Zhao, X. (Centre for Research in Applied Economics, 2012)
This paper employs a dynamic multinomial choice framework to provide new evidence on the effect of health on labour market transitions among older individuals. We consider retirement as a multi-state process and examine the effects of ill-health and health shocks on mobility between full-time employment, part-time employment, self-employment and inactivity. In order to disentangle the roles of unobserved individual heterogeneity and true state dependence, we estimate dynamic panel multinomial logit models with random effects, assuming a first order Markov process and accounting for the initial conditions problem. We also account for potential measurement error in the self-assessed health status by building a latent health stock model and employing measures of health shocks. Using data from the first nine waves of the (2001 - 2009) Household, Income and Labour Dynamics in Australia (HILDA) Survey, we find that both ill-health and health shocks greatly increase the probability of leaving full-time employment towards inactivity. We also find evidence of health-driven part-time and self-employment paths into inactivity.